JURNALISME ADVOKASI PADA ISU PERNIKAHAN ANAK DI SULAWESI SELATAN - Astrid, Andi Fauziah (Komodifikasi, 2019)
The concept of Advocacy Journalism is a genre of journalism that does not speak of the journalist’s objectivity. This concept wants journalists not only to provide information related to certain issues, but also to provide advocacy, choose sources that have a same interest, and try to provide solutions in news. One issue that should be carried out with advocacy journalism is the issue of child marriage in South Sulawesi. Interestingly, this issue was covered by male journalists in onlime mass media. However, with a perspective that emphasizes the principle of advocacy, and then their coverage becomes important to provide further understanding regarding the situation that should be resolved. Moreover, one of the targets of the 2030 Sustainable Development Goals (SDGs) in Indonesia is to eliminate all forms of practices that are harmful to women such as early marriage and female circumcision. For this reason, journalists have the role of assistance to minimize the practice of early marriage, especially in South Sulawesi. The concept of Advocacy Journalism is a genre of journalism that does not speak of the journalist’s objectivity. This concept wants journalists not only to provide information related to certain issues, but also to provide advocacy, choose sources that have a same interest, and try to provide solutions in news. One issue that should be carried out with advocacy journalism is the issue of child marriage in South Sulawesi. Interestingly, this issue was covered by male journalists in onlime mass media. However, with a perspective that emphasizes the principle of advocacy, and then their coverage becomes important to provide further understanding regarding the situation that should be resolved. Moreover, one of the targets of the 2030 Sustainable Development Goals (SDGs) in Indonesia is to eliminate all forms of practices that are harmful to women such as early marriage and female circumcision. For this reason, journalists have the role of assistance to minimize the practice of early marriage, especially in South Sulawesi.